Physical Activity for Adults with Visual Impairments: Impact of Socio-Demographic Factors - Haegele, A. Justin; Zhu, Xihe; Lee, Jihyun; Lieberman, J. Lauren (European Journal of Adapted Physical Activity, 2016)
Little is known about what factors influence physical activity participation for adult-aged individuals with visual impairments. Therefore, the purpose of this study was to explore the impact of socio-demographic factors on the physical activity participation of adults with visual impairments. The international physical activity questionnaire-short form and a socio-demographic factor questionnaire were distributed to individuals with visual impairments. A total of 176 adults (Mage = 47.04, 52.8% female) completed the questionnaires. Physical activity and socio-demographic variables were analyzed descriptively and relationships were explored using correlation analysis and multiple regression analysis. On average, participants reported 413.79 minutes of moderate-to-vigorous physical activity and 2058.52 minutes of sedentary active per week. A significant amount of variance of physical activity was explained by the socio-demographic variables in this study. Of the socio-demographic variables measured, only gender emerges as a significant positive predictor of total weekly physical activity. The results of this study both affirm and conflict with previous research. Unlike previous research focusing on those with visual impairments, this study demonstrated that gender was an important predictor of physical activity. This finding is consistent with population-wide data on individuals without disabilities in the United States.
Keywords: Gender; Disability; IPAQ; Health; Visual Impairment; Blindness